Channel selection of neutron-rich nuclei following fusion-evaporation reactions of light systems - Gibelin, J.; Wiedeking, M.; Phair, L.; Fallon, P.; Basunia, S.; Bernstein, L. A.; Burke, J. T.; Bleuel, D. L.; Clark, R. M.; Cromaz, M.; Deleplanque, M.-A.; Goldblum, B. F.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
a b s t r a c t Experimental results for the minor decay channels of fusion-evaporation in light projectile plus light target systems are presented. These new data were obtained during test campaigns to measure the opening of different decay channels. Experiments were designed to provide relative cross-section information on weakly populated channels for gamma-ray spectroscopy experiments in coincidence with charged-particles. The results are compared to publicly available fusion-evaporation codes. The data follow a simple estimate which is useful in predicting experimental conditions to make the fusion-evaporation reaction a viable nuclear structure tool to study weakly populated light neutron-rich nuclei. & 2011 Elsevier B.V. All rights reserved.